Reflections on the Davos Crisis in the Turkish Press and the Views of Opinion Leaders of the Turkish Jews on the Crisis - BİLEYDİ KOÇ, MALİKE (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2011)
Cooperation between Israel and Turkey has always been important for both states. In line with the historical process, although relations between the two countries have fluctuated from time to time, they have always been maintained at a certain level. An incident that caused tension in relations between the two countries occurred in Davos on January 29, 2009 causing global repercussions. This study analyzes the Davos incident within the context of Ataturk's national policy, and is based on an analysis of the relevant news in the Turkish media, as well as on interviews of the opinion leaders of the Turkish Jews. The analysis aims to evaluate reflections in Israel and Turkey on the 2009 Davos meeting, within the context of Ataturk's national policy and in relation to the views of the opinion leaders. As a result of the analysis of four newspapers with different publication policies, it was determined that conservative newspapers commented that the Davos meeting had been positive for Turkey. On the other hand, a newspaper with a leftist world view reported the news with exactly the opposite comments. In the interviews, opinion leaders evaluated the Turkish prime minister's words as serving to factionalize Turkish Jews, by giving them a feeling of insecurity, and to mobilize radical factions in the society.